PUBLIC PERCEPTION OF VILLAGE FUND USE (Case Study: Sidorejo Village, Kabawetan District, Kepahiang Regency) - Riga Frikassandra; Herri Fariadi; Evi Andriani (LPPM UNIVERSITAS KAHURIPAN KEDIRI, 2025)
This study aims to analyze community perceptions of Village Fund utilization and the factors influencing it in Sidorejo Village. The method used was a survey with a quantitative descriptive approach, involving 64 respondents. Perception levels were analyzed using a Likert scale and percentages, while relationships between variables were tested using Spearman Rank correlation. The results showed that community perceptions of Village Fund utilization were high, with a percentage of 69.27%. The majority of respondents gave a positive assessment, although some still disagreed, pointing out issues related to accountability, public communication, and management effectiveness. Factor analysis showed that education, residential status, occupation, and age had a significant influenceon community perceptions, while gender did not. Education had the strongest correlation (r = 0.869), followed by occupation (r = 0.776), residential status (r = 0.713), and age (r = 0.440). The higher the community's education level, participation, and relevance of work to village programs, the more positive their perceptions of the transparency and benefits of the Village Fund.